A pattern language : towns, buildings, construction - Alexander, Christopher; Ishikawa, Sara; Silverstein, Murray (New York : Oxford University Press, 1977)
v. 1. The timeless way of building--v.2. A pattern language--v.3. The Oregon experiment.
Companion volume to The timeless way of building and The Oregon experiment.
boek
Keywords: Symbolism in architecture; Semiotics